Occupational therapy : perspectives and processes - Hagedorn, Rosemary, ....- (Edinburgh : Livingstone, 1995)
PART 1 PERSPECTIVES Occupational Therapy : A Retrospective. Definitions. In Search of the Core. The Person. Occupation. Environment. The Therapist. The Prescription of Activities as Therapy. Occupational Therapy : Macroanalysis. The Productive Self. PART 2 PROCESSES Case Management. Intervention. Assessment and Evaluation. Occupational Analysis and Adaptation. Environmental Analysis and Adaptation. Therapeutic Use of Self. Management of Resources. PART 3 PERSPECTIVES and PROCESSES Postscript: Perspectives and Processes.
Keywords: Ergotherapie